2022
DOI: 10.1038/s41419-022-04718-8
|View full text |Cite
|
Sign up to set email alerts
|

SLC25A38 as a novel biomarker for metastasis and clinical outcome in uveal melanoma

Abstract: Risk of metastasis is increased by the presence of chromosome 3 monosomy in uveal melanoma (UM). This study aimed to identify more accurate biomarker for risk of metastasis in UM. A total of 80 patients with UM from TCGA were assigned to two groups based on the metastatic status, and bioinformatic analyses were performed to search for critical genes for risk of metastasis. SLC25A38, located on chromosome 3, was the dominant downregulated gene in metastatic UM patients. Low expression of SLC25A38 was an indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Gao et al (2021) found that SLC2A3 was correlated with EMT and immune signature in colorectal cancer. Fan et al (2022) verified that SLC25A38 was a In conclusion, this study first identifies the prognostic value of FLVCR2 in patients with AML. FLVCR2 expression is associated with immunocyte infiltration, such as NK cells, T cells, or macrophages in AML.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Gao et al (2021) found that SLC2A3 was correlated with EMT and immune signature in colorectal cancer. Fan et al (2022) verified that SLC25A38 was a In conclusion, this study first identifies the prognostic value of FLVCR2 in patients with AML. FLVCR2 expression is associated with immunocyte infiltration, such as NK cells, T cells, or macrophages in AML.…”
Section: Discussionsupporting
confidence: 60%
“… Gao et al (2021) found that SLC2A3 was correlated with EMT and immune signature in colorectal cancer. Fan et al (2022) verified that SLC25A38 was a novel biomarker for metastasis and clinical outcome in uveal melanoma. Our study focused on identifying FLVCR2 as a novel biomarker for AML, which may be an independent prognostic factor that influenced tumorigenesis and tumor immunology in AML progression.…”
Section: Discussionmentioning
confidence: 67%
“…RNF43, SLC25A38, and CALHM2 are listed among the most differential UM survival genes based on transcriptome data from 80 UM cases from the TCGA dataset (26). The downregulation of SLC25A38, located on chromosome 3, was associated with enhanced migration of UM cells and promoted metastasis in mice models (44).…”
Section: Discussionmentioning
confidence: 94%
“…RNF43, SLC25A38, and CALHM2 are listed among the most differentially expressed UM survival genes based on transcriptome data from 80 UM cases from the TCGA dataset (26). The downregulation of SLC25A38, located on chromosome 3, was associated with enhanced migration of UM cells and promoted metastasis in mouse models (44). SLC25A38 is a mitochondrial glycine transporter that induces caspasedependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%